Zeyheria montana Mart. (Bignoniaceae) as source of antioxidant and immunomodulatory compounds with beneficial effects on intestinal inflammation - Seito, Leonardo Noboru [UNESP]; Sforcin, Jose Mauricio [UNESP]; Bastos, Jairo Kenupp; Di Stasi, Luiz Claudio [UNESP] (Wiley-Blackwell, 2015)
Objectives: Zeyheria montana is a medicinal plant used in Brazilian folk medicine for treating skin affections, ulcers, inflammation and diarrhoea, and as an antisyphilitic and antiblenorrhagic agent, but little is known about its mechanisms of action. Herein, a bio-guided assay was carried out to further evaluate its antioxidant and immunomodulatory effects, and the possible benefits on experimental intestinal inflammation. Methods: Extracts, partitions, fractions and isolated compounds were tested for inhibition of lipid peroxidation. Isolated compounds were tested in vitro for its antioxidant and immunomodulatory action prior to in-vivo evaluation in trinitrobenzenesulfonic acid-induced rat colitis. Key findings: Two major compounds were identified in the leaf dichloromethane extract: 3-hydroxy-5,7,4-trimethoxyflavone and 6-hydroxy-5,7-dimethoxyflavone, which exhibited an antioxidant activity. The compounds protected the colonic glutathione levels in more than 90% despite the absence of protection against the gross macroscopic colonic damage. In addition, the compounds inhibited IL-1 ss secretion by macrophages in 91.5% and 72.7% respectively, whereas both reduced IL-6 secretion in about 44.5%. Conclusions: The major active compounds from Z.montana leaves exerted antioxidant and immunomodulatory effects, endorsing the use of Z.montana in folk medicine as an anti-inflammatory agent. However, further investigation is still needed regarding medicinal plants and the identification of candidate compounds for the treatment of the inflammatory bowel diseases.
Keywords: Antioxidant activity; Flavonoids; Immunomodulatory activity; Inflammatory bowel disease; Zeyheria montana (Bignoniaceae)